Process of ectopic tooth formation in the maxillary sinus: follow-up observation of one case. Issue 12 (December 2019) - Liu, Jinfeng; Zhou, Mo; Liu, Qitong; He, Xiaolin; Wang, Ningyu
Objective: This study was performed to investigate the process of ectopic tooth formation. Methods: A patient with an ectopic tooth was followed for 6 years. The tooth size andmineralization were evaluated by paranasal sinus computed tomography every 3 years. Results: The ectopic tooth was present in the nasal crest of the maxilla and did not change significantly during the 6-year follow-up period. However, the patient developed a new ectopic tooth in the maxillary sinus (ETm). This tooth, located in the posterior wall of the left maxillary sinus, initially appeared as a small region of soft tissue on computed tomography. After 3 years, the area of mixed density had significantly increased, and some of it had significantlymineralized to form an ETm. After 6 years, the ETm had furthermineralized and enlarged in situ. The width between the left and right sides of the ETm in 2018 (9.08 ± 2.09 mm) was significantly larger than that in 2015 (7.51 ± 2.18 mm), indicating that ETm formation is a gradual process ofmineralization . Conclusion: Ectopic teeth can gradually form by in situ mineralization after adolescence, suggesting that ectopic teeth are genetically regulated and result from a programmed formation process occurring at a specific time point.